The new environmentalism? [ civil society and corruption in the enlarged EU - Torsello, Davide (Urban anthropology, 2012)
Comparative in approach, The New Environmentalism? provides new insights into the emergence of strong civic movements at local and trans-local levels, in resistance to citizens' sense of increasing alienation from political participation and decision making. As such, it will be of interest to anthropologists, sociologists and political scientists concerned with questions of legitimacy, corruption and activism